Polemic on the Legitimacy of Proof of E-Court Trial at the State Administrative Court (Harmonization of Legal Courts and Information Technology in the Covid-19 Pandemic Era) - Andrean Al Ikhsan; Rachman Adi Wibowo (Universitas Negeri Semarang, 2023)
Amid the global upheaval caused by the Covid-19 pandemic, this study navigates the challenges presented by the perilous situation, focusing specifically on the transformation of legal proceedings. The pandemic, posing risks to public health, compelled the imposition of widespread restrictions, limiting various community activities and direct interactions. This shift had profound implications for the justice system, prompting a departure from the conventional practice of open and in-person court proceedings. In response to these unprecedented circumstances, the legal arena saw the emergence of online courts, commonly known as e-courts, as an alternative to traditional court setups. The study seeks to critically examine the effectiveness and legitimacy of e-courts during this tumultuous period. Utilizing a literature study method, the research delves into relevant books and literature, emphasizing the collection of data to assess the harmony between legal court proceedings and information technology in the context of the pandemic. The primary goal is to scrutinize the polemics and challenges surrounding the implementation of e-courts, particularly in the State Administrative Court. As the study unfolds, it reveals a nuanced perspective on the harmonization of legal courts and information technology during the Covid-19 pandemic. The discussion extends to the legitimacy of proof in e-court trials, with a specific focus on the State Administrative Court. The analysis underscores the necessity of maintaining a balance between conventional and electronic trial methods to ensure a comprehensive and reliable legal system. In addition, the research contends that despite the convenience offered by e-courts, doubts persist regarding the legitimacy of evidence presented in electronic trials, particularly in the administrative context. The findings contribute valuable insights that can inform future legislative efforts, guiding the harmonization of legal courts and information technology. Ultimately, the study aims to foster the development of a robust legal framework that addresses the polemics surrounding e-court trials, enhancing their legitimacy and efficacy in the ongoing and post-pandemic era.